2022
DOI: 10.1037/pag0000678
|View full text |Cite
|
Sign up to set email alerts
|

Personality and subjective age: Evidence from six samples.

Abstract: Subjective age is associated with health-related outcomes across adulthood. The present study examined the cross-sectional and longitudinal associations between personality traits and subjective age. Participants (N > 31,000) were from the Midlife in the United States Study (MIDUS), the Health and Retirement Study (HRS), the National Health and Aging Study (NHATS), the Wisconsin Longitudinal Study Graduate (WLSG) and Siblings (WLSS) samples, and the English Longitudinal Study of Aging (ELSA). Demographic facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…There might also be recall biases when individuals report their pain in the past 4 weeks, with individuals who had pain at the time of assessment potentially reporting stronger pain levels for the entire 4 weeks, whereas individuals with no current pain complaints might rather neglect prior pain complaints within the past 4 weeks. Likewise, with regard to covariates, there may be additional factors at work that have to be taken into account, such as neuroticism, as greater neuroticism is related with more pain and symptom reporting (Costa & McCrae, 1987; Wettstein et al, 2022), with a lower threshold from which on an individual perceives pain as threatening (Goubert et al, 2004), and with an older subjective age (Stephan, Sutin, Kornadt, et al, 2022). Adjusting to health conditions such as pain might be harder for individuals who score higher on neuroticism, as these individuals have been found to exhibit a higher reactivity to stressors (e.g., Bolger & Schilling, 1991; Suls & Martin, 2005)—and these stressors might include pain—and they tend to use passive and ineffective coping strategies (e.g., Watson & Hubbard, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…There might also be recall biases when individuals report their pain in the past 4 weeks, with individuals who had pain at the time of assessment potentially reporting stronger pain levels for the entire 4 weeks, whereas individuals with no current pain complaints might rather neglect prior pain complaints within the past 4 weeks. Likewise, with regard to covariates, there may be additional factors at work that have to be taken into account, such as neuroticism, as greater neuroticism is related with more pain and symptom reporting (Costa & McCrae, 1987; Wettstein et al, 2022), with a lower threshold from which on an individual perceives pain as threatening (Goubert et al, 2004), and with an older subjective age (Stephan, Sutin, Kornadt, et al, 2022). Adjusting to health conditions such as pain might be harder for individuals who score higher on neuroticism, as these individuals have been found to exhibit a higher reactivity to stressors (e.g., Bolger & Schilling, 1991; Suls & Martin, 2005)—and these stressors might include pain—and they tend to use passive and ineffective coping strategies (e.g., Watson & Hubbard, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…While most studies have considered age identity to be a relatively stable variable, Hughes and Touron offer a novel account of how daily life offers a variety of situational contexts and experiences that directly impact the age a person feels at a given moment (45). It has also been found that retirement intentions positively predicted subjective age (46), while personality traits with higher scores such as extroversion, openness, agreeableness and conscientiousness were associated with a younger subjective age (47). The closest study to this paper is Liu et al, who focused on examining the impact of social engagement behaviors on the old age identities of the Chinese elderly and found that political engagement behaviors of the elderly help delay the onset of old age (11).…”
Section: Literature Reviewmentioning
confidence: 99%